Upaya Meningkatkan Hasil Belajar IPA Materi Pembuatan Makanan pada Tumbuhan Hijau dengan Menggunakan Media Ular Tangga pada Siswa Kelas V Sekolah Dasar - Matrona Owa (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The objectives of the study are to describe the process of science study and learn the making of green plants food by using snakes and ladders gamein the fifth grade students of SD Inpres Belang. (2) to find out the science study result  the making of green plants food by using snakes and ladders game in the fifth grade students of SD Inpres Belang This research is classified as classroom action research.Penelitian ini menggunakan model penelitian tindakan kelas. The method used  in this research is  qualitative and quantitative method. Qualitative method is a method to try to understand and individual from the studied subject. Meanwhile the quantitative method is a method that use the calculation the result of the study such in numbers Sedangkan Kuantitatif pendekatan  yaitu pendekatan yang digunakan dalam perhitungan hasil belajar  berupa angka-angka. The subjects of the study were the 20 fifth grade students of SD Inpres Belang.From the result of the study, the use of snakes and ldders game in science study and learn process in making of green plants food improving the result of the fifth grade students of SD Inpres Belang  2019/2020. This can be seen in the result analysis in first cycle 65 % avarage, and second cycle 90% in verygood category.